The outcome of the Uruguay Round : an initial assessment : supporting papers to the trade and development report, 1994 - United Nations Conference on Trade and Development Secretariat; United Nations Conference on Trade and Development (New York : United Nations, 1994)
The papers attempt to provide a clearer understanding of the main understanding of the main features of the Final Act embodying the results of the Uruguay Round and to set out the parameters of the comprehensive analysis and assessment of income of the Round Agreements and their negotiating history.
.
Includes bibliographical references.
opc 20/12/16
Loans
Keywords: Free trade; Tariff--Law and legislation; Uruguay Round (1987-1994); General Agreement on Tariffs and Trade (Organization); World Trade Organization; Foreign trade regulation; International trade; Commercial policy